SEJARAH DAN PERKEMBANGAN PERADILAN ISLAM MASA KEMERDEKAAN SAMPAI REFORMASI - Hartono, Hartono; Basir, Muchammad Abdul; Hadi, Muh Din Syamsul; Nurhaliza, Febriana; Hanafi, Lailatul Maulidya (Al-Usroh : Jurnal Hukum Keluarga Islam, 2024)
This study examines the history and development of Islamic judiciary in Indonesia from the independence period to the reform era. The main focus is to identify structural, legal, and role changes of the Islamic judiciary in the context of political and social dynamics during this period. In the early days of independence, the Islamic judiciary was part of the national legal system and faced various challenges in enforcing Sharia law. Significant changes occurred throughout the Old Order, New Order, and especially during the reform era, marked by decentralization and democratization that strengthened the position of the Islamic judiciary. This study employs a historical approach and policy analysis to explore the transformation of the Islamic judiciary in response to various political and social changes in Indonesia. The results of the research indicate that the Islamic judiciary has developed significantly, adapting to constitutional and legal changes, and plays an important role in law enforcement in Indonesia. However, there are still challenges in the full integration of the Islamic judiciary into the national legal system that need to be addressed.